IDENTIFIKASI MEDIA PEMBELAJARAN KIMIA BAGI PESERTA DIDIK DIFABEL NETRA DAN RUNGU PADA SMA/MA INKLUSI DI YOGYAKARTA - Kamaludin, Agus (INKLUSI, 2015)
Identification of learning media is the first step of series activities in inclusive setting research. The availability of chemistry learning media, obstacles encountered by teachers in modifying the media, and solutions that can be done to meet the needs of chemistry learning media for blind and deaf students ininclusive school in Yogyakarta need to be investigated. A descriptive qualitative research using data collecting techniques of observation, interview, attitude scale filling and document analysis has done. This research finds the fact that chemistry learning media for blind and deaf students are very limited, it is caused by the fact that the teachers had never follow any training for developing chemistry learning media for disabled student. As a recommendation, the solution to fulfill the needs of chemistry learning media is by providing training for teacher and developing media through undergraduate students’ final thesis.